TeaMiD: a comprehensive database of simple sequence repeat markers of tea. (11th March 2020) - Dubey, Himanshu; Rawal, Hukam C; Rohilla, Megha; Lama, Urvashi; Kumar, P Mohan; Bandyopadhyay, Tanoy; Gogoi, Madhurjya; Singh, Nagendra Kumar; Mondal, Tapan Kumar
Abstract: Tea is a highly cross-pollinated, woody, perennial tree. High heterozygosity combined with a long gestational period makes conventional breeding a cumbersome process. Therefore, marker-assisted breeding is a better alternative approach when compared with conventional breeding. Considering the large genome size of tea ( 3 Gb), information about simple sequence repeat (SSR) is scanty. Thus, we have taken advantage of the recently published tea genomes to identify large numbers of SSR markers in the tea. Besides the genomic sequences, we identified SSRs from the other publicly available sequences such as RNA-seq, GSS, ESTs and organelle genomes (chloroplasts and mitochondrial) and also searched published literature to catalog validated set of tea SSR markers. The complete exercise yielded a total of 935 547 SSRs. Out of the total, 82 SSRs were selected for validation among a diverse set of tea genotypes. Six primers (each with four to six alleles, an average of five alleles per locus) out of the total 27 polymorphic primers were used for a diversity analysis in 36 tea genotypes with mean polymorphic information content of 0.61–0.76. Finally, using all the information generated in this study, we have developed a user-friendly database (TeaMiD; http://indianteagenome.in:8080/teamid/) that hosts SSR from all the six resources including three nuclear genomes of tea and transcriptome sequences of 17 Camellia wild species. Database URL: http://indianteagenome.in:8080/teamid/